The professional stranger : an informal introduction to ethnography - Agar, Michael (New York : Academic Press, 1980)
This edition of an introductory text opens with a chapter that brings ethnography up-to-date and aims it toward the next century. At a time when numerous disciplines, organizations, and communities are discovering ethnography, Agar shows how the fundamentals endure.
Bibliography: p. 205-213.
Keywords: Ethnology -- Field work; Ethnology -- Methodology